Power, interdependence, and nonstate actors in world politics - Milner, Helen V., 1958-; Moravcsik, Andrew (Princeton University Press, 2009)
Since they were pioneered in the 1970s by Robert Keohane and others, the broad range of neoliberal institutionalist theories of international relations have grown in importance. In an increasingly globalized world, the realist and neorealist focus on states, military power, conflict, and anarchy has more and more given way to a recognition of the importance of nonstate actors, nonmilitary forms of power, interdependence, international institutions, and cooperation. Drawing together a group of leading international relations theorists, this book explores the frontiers of new research on the.